Gaze Patterns in Auditory-Visual Perception of Emotion by Children with Hearing Aids and Hearing Children - Wang, Yifang; Zhou, Wei; Cheng, Yanhong; Bian, Xiaoying (Frontiers in Psychology, 2017)
This study investigated eye-movement patterns during emotion perception for children with hearing aids and hearing children. Seventy-eight participants aged from 3 to 7 were asked to watch videos with a facial expression followed by an oral statement, and these two cues were either congruent or incongruent in emotional valence. Results showed that while hearing children paid more attention to the upper part of the face, children with hearing aids paid more attention to the lower part of the face after the oral statement was presented, especially for the neutral facial expression/neutral oral statement condition. These results suggest that children with hearing aids have an altered eye contact pattern with others and a difficulty in matching visual and voice cues in emotion perception. The negative cause and effect of these gaze patterns should be avoided in earlier rehabilitation for hearing-impaired children with assistive devices.